Escrevendo histórias e preservando memórias: migração do processo judicial físico para o sistema processo judicial eletrônico-PJE no Tribunal de Justiça de Pernambuco (2020-2022). - Souza, Joselma Maria Santana Correia de (2022)
This research aims to analyze the migration of the Physical Judicial Process to the Electronic Judicial Process System-PJE, at the Pernambuco Court of Justice (TJPE), between 2020 and August 2022. The time frame begins in January 2020, with the beginning of the migration, which has the characteristic of preserving the numbering and date of the beginning of the process in the judiciary, as well as the possibility for the parties to access the records without having to travel to the most distant forums. The processes are a historical source, as they contain the demands of individuals, the decisions of the magistrates, the laws of the period and the social actors, whose procedural universe allows us to make a social and cultural analysis of the historical period of the analyzed process. This migration to the PJE preserves the memory of these events, o it allows the processes to be accessed by more individuals and researchers. The theoretical foundation resides in the studies of E. Thompson, Darnton e Jacques Le Goff, on History, Memory and Time. The methodology will be qualitative and descriptive, with data collection in the following modalities: exploratory, classification and analysis of documentation, access to the PJE System, Laws and Regulations on digitization and migration and, demonstrating in a Digital Booklet, functionalities that range from help to better manage the Panel of the Procedural Representative, Public Defender, Prosecutor, Civil Police Delegate, Military, Firefighter, Federal, Federal Highway, Municipal, State and Federal Prosecutor.